1973
DOI: 10.1002/jez.1401830210
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of sialic acid‐containing components of embryonic cell surfaces

Abstract: Sialic acids such as N-acetylneuraminic acid have been found at the surfaces of various cells. They may play a n important role in intercellular adhesion and hence in animal morphogenesis. This work demonstrates sialic acid at the surfaces of seven-day chick embryo neural retinal cells and its regeneration after enzymatic removal.Neural retinas were excised and dissociated with trypsin. The cells were incubated in a solution of Vibrio cholerae neuraminidase. The enzymatic treatment released sialic acid which w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1974
1974
1990
1990

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…In contrast, Kemp (10,11) found that the presence of neuraminidase decreased the aggregation of embryonic chick muscle cells harvested by trypsinization . Measurement of the effect of neuraminidase on the reaggregation of trypsin-dissociated neural retina cells did not yield reproducible results (12) .…”
mentioning
confidence: 98%
“…In contrast, Kemp (10,11) found that the presence of neuraminidase decreased the aggregation of embryonic chick muscle cells harvested by trypsinization . Measurement of the effect of neuraminidase on the reaggregation of trypsin-dissociated neural retina cells did not yield reproducible results (12) .…”
mentioning
confidence: 98%
“…One possible explanation would be that acidic groups regenerated after digestion. Yet, such regeneration should be minimal for cells stored at 0 C, especially since electrophoresis took place immediately upon digestion and washing (Kruemer 1966, Collins et al 1973. We find it more likely that deeply sited negative groups moved into the plane of shear ( Weiss 1969, Singer & Nicolson 1972.…”
Section: Discussionmentioning
confidence: 87%
“…It could be argued that the absence of an effect was due to partial or complete loss of the glycocalyx during the cell isolation procedure (Schanne, Bkaily & Fermini, 1983;Lee & Hsu, 1987). However, sialic acid residues on the cell surface regenerate in culture within 24 hr (Kraemer, 1966;Collins, Holland & Sanchez, 1973;B. Fermini, unpublished results) and can be detected on cardiac myocytes after several days in culture (Frank et al, 1977;Barton, Markwald & Nathan, 1982).…”
Section: Sialic Acid Residues and The Surface Chargementioning
confidence: 89%